Potential of Naringin, Hesperidin and Rutin: Phytochemical and Biological Benefits - Kaur, Loveleen; Arora, Athrv; Gupta, Shifali; Kumari, Sapna; Garg, Madhukar; Chopra, Hitesh (Scripta Medica, 2025)
This review provides an overview of the recent biological and phytochemical advancements of the compounds such as naringin, hesperidin and rutin, which are bioactive flavonoids mainly present in citrus fruits with substantial therapeutic potential. Naringin possesses beneficial properties such as antioxidant, antitumor, antiviral and many more discussed in the article. Studies have indicated that naringin aids in slowing the progression of cancer in different regions of the body. Its anticancer effects are so extensive that it can change how cells interact and transmit signals, decrease the production of specific proteins such as cytokines and growth factors, and also impede the proliferation of cancer cells. Hesperidin has demonstrated notable anticancer and neuroprotective potential. Rutin is widely recognised or known for its venotonic, anti-thrombotic, anti-inflammatory and anticancer properties. This review offers in-depth analysis and details of their constituents and their industrial applications.